Alumni Breakfast - George Soros' Speech
Audio recording of the first Alumni Breakfast within the Second Annual Alumni Leadership Forum, held in conjunction with CEU's Tenth Anniversary celebrations. President and Rector Yehuda Elkana delivers a speech in which he explains the importance of staying in touch with the graduates and how necessary it is to create a network between them. President and Rector of CEU, Yehuda Elkana asks Alumni to stay involved in university affairs. He then invites the Representative of Alumni Leadership Forum to say a few words. Next two representatives of the Alumni Fundraising Committee announce the Alumni Scholarship Campaign results. The Alumni Breakfast continues with a speech delivered by Founder of CEU and Chairman of the Board of Trustees, George Soros.